Peran Guru Dalam Penanaman Karakter Kemandirian Dan Tanggung Jawab Dalam Proses Pembelajaran(Studi Kasus Pada Guru Pendidikan Pancasila dan Kewarganegaraan di Madrasah Tsanawiyah Negeri 1 Surakarta) - Winarsih, Erwin; , Prof. Dr. Bambang Sumardjoko, M. Pd (2017)
This study aims to describe the role of teachers in the inculcation of independence characters and the responsibility in learning process of the case study in Pancasila and Civics Education teachers in Madrasah Tsanawiyah Negeri 1 Surakarta), including the characteristics, the role of teachers, supporting factors and inhibiting factors. This research uses the qualitative research employing the case of study. Technique of collecting data use observation, interview, documentation. The data validity with triangulation of data sources and technique of collecting data. The instrument data processing uses interactive analysis through collecting data, reduction, presentation and drawing conclusions. The results of this study showed that the characteristics of the inculcation of independence characters and responsibility is the teacher inculcate the value of honesty to the learners at the time of daily repetition or repetition of class increase that students do repetition questions on their own, independent without the help of friends or cheats and teachers remind students to always obey the school order. The role of teachers are to motivate to the learners, to teach to be independent, to give a reprimand to the students. Supporting factors in the planting of independence and responsibility characteristic is the support of the school, family support and student learning environment. Factors that impede the cultivation of character independence and responsibility of the age of students who are stil unstable, the lack of motivation from within students, and the association of students.